Social Acceptance for Patients with Pulmonary Tuberculosis from Their Own Perspective in Rafsanjan, Iran: A Cross Sectional Study - Rzea Bidaki; Marzie Bagheri Mahonaki; Ziba Shabani Shahrbabaki; Hamid Bakhshi Aliabad; Maryam Sadeh (Shahid Sadoughi University of Medical Sciences, 2022)
Introduction: Social acceptance is defined as the support by social network for patients via family, friends and colleagues that often reason the better management and prognosis. If the social acceptance is significantly low in patients with chronic diseases like tuberculosis, an appropriate plan can raise the level of knowledge and the culture of the community to enhance the level of patient and community's acceptance. The authors aim to evaluate social acceptance and related factors in these patients in Rafsanjan. Methods: This was a descriptive and cross-sectional study. It was conducted on 29 pulmonary TB (tuberculosis) patients who had referred to Rafsanjan city health center in Iran in 2014. They were selected by census method. The Marlou-Crown questionnaire was completed by patients, and the scores were calculated based on the questionnaire key using SPSS 16. T-test, Fisher and chi-square tests were used for evaluation, and the significance level was P-value <0.05. Results: Results showed that the frequency social acceptance among patients was moderate to high (62%) and moderate to low (38%). Fifteen (52%) patients were male and 14 (48%) were female whose age range was 8 to 90.  Among the variables of age, sex, education, place of residence, nationality and family history of patients, the relationship between age، nationality, positive family history of TB and social acceptance was significant (P-value <0.05). Conclusion: This study concludes that older patients, those with a family history of TB, and migrant patients have higher social acceptance (P-value <0.05).